Electrical energy production by using waste exhaust energy of internal combustion diesel engines - Temizer, Ilker; Ilkilic, Cumali (Pamukkale Univ, 2017)
In this study, a prototype that works in accordance with the working principles of thermoelectric generator has been applied to the exhaust system of an internal combustion diesel engine. The aim is to transform heat energy that is discharged into the atmosphere into a usable electrical energy. Two different fluids have been used in the systems in order to create different temperatures that constitute the working conditions of thermoelectric module. One of them is the exhaust gases that are used to create a hot surface. The other fluid is cooling water that enables to create differential temperature that is necessary for thermoelectric module. 40 thermoelectric modules that are placed on octagonal structure composed of aluminum alloy material are connected to each other electrically. The performance of thermoelectric generation systems has been examined in terms of changing speed and load in the engine. At the same time, the vehicle battery has been charged by transferring the electrical energy to converters.
Keywords: Waste heat recovery; Thermoelectric generation; Diesel engine